AWMS automated weather monitoring system for remote microclimate applications - Tibajia, Gino Virgilio B.
Small scale patterns of climate resulting from the influence of topography, urban forms, bodies of water and vegetation, are known as microclimates. Microclimate information is important in determining the factors that influence ecological processes which reflect subtle changes on the ecosystem. Satellite images, which provide most weather information, cannot provide this information due to its high spatial resolution, typically from 1 kilometer to 20 kilometers. The spatial resolution can be improved by increasing the number of weather stations to provide additional on-site weather data. However, there are only less than 50 weather stations deployed in the Philippines. The Automated Weather Monitoring System (AWMS) aims to provide weather monitoring capabilities as well as microclimate data and information. A weather station measures the common environmental variables, such as air temperature, wind velocity, and rain fall. A base station collects weather data from multiple weather stations via SMS and stores the data in a database for data display, manipulation and analysis. The system uses pre-calibrated sensors for temperature, wind velocity and precipitation for the accuracy of the measurements. A Z8 Encore! Microcontroller is used to implement this design. The weather station is also equipped with a Multimedia Card for data logging and a GSM Module for SMS requests from the end users, as well as for communication to the base station. The weather station is powered using a solar power system for the full autonomy of its operation. Solar panels harness available incoming solar radiation to charge the battery of the system. A high capacity Sealed Lead-Acid Battery serves as the backup source of power for the system when solar radiation is insufficient. The custom-designed weather station was able to gather weather data autonomously with an acceptable accuracy. The rainfall measurements of the AWMS were confirmed to have no errors. The wind speed measurements of the AWMS have a maximum error of + 1 mph. in reference to the Davis Weather Wizard. The temperature measurements however, require linear compensation in the microcontroller firmware. The designed solar power system was able to sustain the operation of the weather station continuously for two weeks. The collection and storage of data at the base station was also made autonomous for prolonged deployment and monitoring.